Green infrastructure-based hydrological modelling, a comparison between different urban districts, through the case of Szeged, Hungary - CseteÁkos Kristóf; Gulyás, Ágnes (Hungarian Geographical Bulletin, 2021)
Because of the climate uncertainties caused by climate change and the growing urban areas, today’s cities face new environmental challenges. The impervious artificial elements change the urban water cycle. Urban districts with inadequate water infrastructure and treatment can be a major source of environmental risks, like urban flash floods. Modern cities need to be prepared for the changing environment in a sustainable way, which can be realised with the help of green infrastructure. The primary role of the green infrastructure is mitigation, such as surface runoff reduction and retainment. The aim of our research is to examine urban district scale data about the role of green infrastructure in urban water management. Hydrological models can provide adequate data about the surface runoff, infiltration and the mitigating effect of vegetation (interception and evaporation). We compared two significantly different urban districts (downtown and housing estate area), based on land cover and vegetation data. The analysis of the districts of Szeged (Hungary) suggests that the vegetation can significantly contribute to the reduction of surface runoff. Differences between these urban districts can be quantified, thus, these data can serve as a basis for urban water management planning processes.